Nanomaterials and nanotechnology for sustainable energy - Igor Hut; Svetlana S. Pelemiš; Dragoljub Lj. Mirjanić (Zaštita Materijala)
The use of nanotechnology to develop a suite of sustainable energy production schemes is one of the most important scientific challenges of the 21st century. The challenge is to design, to synthesize, and to characterize new functional nanomaterials with controllable sizes, shapes, and/or structures. Nanotechnology is generating a lot of attention these days and therefore building great expectations not only in the academic community but also among investors, the governments, and industry. This paper, explores some of the possible implementations of nanotechnology for new and improved methods of energy conversion, considering a need for this to be done without compromising our environment. Its unique capability to fabricate new structures at atomic scale has already produced novel materials and devices with great potential applications in a wide number of fields. Focus is given to important role of nanomaterials, preparation and characterization some of nanomaterials important for sustainable energy, dye sensitized solar cels and hydrogen production technology.